Effect of Oxaliplatin-Loaded Poly (d,l-Lactide-co-Glycolic Acid) (PLGA) Nanoparticles Combined with Retinoic Acid and Cholesterol on Apoptosis, Drug Resistance, and Metastasis Factors of Colorectal Cancer - Ana Luiza C. de S. L. Oliveira; Raimundo Fernandes de Araújo Júnior; Thaís Gomes de Carvalho; Alan B. Chan; Timo Schomann; Filippo Tamburini; Lioe-Fee de Geus-Oei; Luis J. Cruz (Pharmaceutics, 2020)
Apoptosis signaling pathways, drug resistance, and metastasis are important targets to develop new cancer treatments. We developed cholesterol-coated Poly(d,l-Lactide-co-Glycolic Acid) (PLGA) nanoparticles for effective encapsulation and delivery of retinoic acid and oxaliplatin to analyze their antitumor activity in colorectal cancer. The cell viability and proliferation of tumoral cells lines (CT-26 and SW-480) decreased when compared to control in vitro after treatment with the nanoparticles. In addition, apoptosis of CT-26 cells increased. Importantly, cytoprotection of nontumor cells was detected. Expression of pro-apoptotic proteins was upregulated, while anti-apoptotic proteins were downregulated either in vitro or in vivo. In addition, drug resistance and metastasis factors were downregulated in vivo. Human colorectal tumors that highly expressed BCL-2 and Ki-67 had a greater tendency towards death within 60 months. Our results show that loading oxaliplatin combined with retinoic acid and cholesterol in a nanoparticle formulation enables determination of optimal antitumor activity and subsequent treatment efficacy.